Strategy for the Development of International Training At the National Financial Audit Training Agency (Badan Diklat Pemeriksaan Keuangan Negara) - Yanto, Budi; Lestari, Ni Putu Nina Eka (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to identifies the strategy for the development of international training at Badiklat PKN (the National Financial Audit Training Agency). This study adopts a qualitative approach to answer the research questions, utilizing two primary methods: observation and in-depth interviews. The study recommends a growth-focused strategy for Badiklat PKN’s international training programs, which includes enhancing infrastructure, increasing human resources, improving training materials. In conclusion, this research underscores the significant role of organizational environment in shaping policies for international training at Badiklat PKN, with a focus on enhancing Badan Pemeriksa Keuangan's global position through high-quality training programs